Improving Customer Satisfaction through Trust in "Bandung Tour on Bus (Bandros)" by Taking Into Account The Contribution of Service Quality and Brand Image - Soerjanto, Soerjanto; MH Nainggolan, Bonifasius (Majalah Ilmiah Bijak, 2022)
The importance of trust in bridging the gap between service quality, brand image, and customer satisfaction is investigated in this study. Respondents to this study were tourists who used Bandros services.  Questionnaires were distributed to travellers of Bandros users using purposive sample techniques with the final sample number of 300 respondents.   The data was collected through questionnaires on Bandros bus passengers in Bandung, West Java, Indonesia. Smart PLS-SEM 3.2.9 is used to assess conceptual models.     Although service quality and trust were essential elements in increasing customer satisfaction, the data showed that brand image was not. The quality of service and the brand image significantly influence building trust. Service quality, contentment, and brand image are all mediated through trust. This study provides new insights into how "Bandros" builds customer satisfaction.   The model demonstrates how trust is crucial in mediating brand image and consumer satisfaction. In addition, research conducted in the tourist transportation service industry is believed to have unique characteristics compared to other sectors.